Angolan politics and the portuguese press : media-politics interaction in a context of political crisis - Carvalho, Anabela (1996)
The goal of this paper is to examine the role of the Portuguese press in Angolan political dynamics during 1991/1992 and in the political relations between Portugal and Angola at two main levels: the effects of press on political decision-making and on political action and the ways political actors use the media. In order to fulfill these objectives I interviewed about 20 Portuguese and Angolan political decision-makers, diplomats and journalists, and analyzed around 200 news articles. The views of those politicians and journalists about the interaction between media and politics will be presented in the paper.